L’animation à l’université française, un enseignement en quête d’identification - Lucie Merijeau et Sébastien Roffat (Mise au Point)
As few French academic publications have been devoted to Animation dealing with aesthetic issues, some researchers have focused their attention more fully on this concern. However they did not succeed in the creation and persistence of courses, seminars or symposiums. Every attempt at studying Animation remained isolated and without the fundamental pedagogical logic which is relevant of the departments of Cinema Studies in France. In this article, we will address the educational paradigms of Animation in French universities, with a focus on what makes these paradigms so specific when compared to other cinemas. We will rely on interviews conducted with teachers and researchers in Animation, and on our own teaching experiences to make assumptions, which will make for more ample reflection.